Desulphurization of Simulated Oil Using SAPO-11 with CNT’s as Adsorbent: A Kinetic Study - Jabaar, Gaith K.; Al-Jendeel, Hayder A.; Alsheikh , Yasir Ali (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
In this study, sulfur was removed from imitation oil using oxidative desulfurization process. Silicoaluminophosphate (SAPO-11) was prepared using the hydrothermal method with a concentration of carbon nanotubes (CNT) of 0% and 7.5% at 190 °C crystallization temperature. The final molar composition of the as-prepared SAPO-11 was Al2O3: 0.93P2O5: 0.414SiO2. 4% MO/SAPO-11 was prepared using impregnation methods. The produced SAPO-11 was described using X-ray diffraction (XRD) and Brunauer-Emmet-Teller (N2 adsorption–desorption isotherms). It was found that the addition of CNT increased the crystallinity of SAPO-11. The results showed that the surface area of SAPO-11 containing 7.5% CNT was 179.54 m2/g, and the pore volume was 0.317 cm3/g. However, the surface area of SAPO-11 containing 0% CNT was 125.311 m2/g, and pore volume was 0.275 cm3/g, while nanoparticles with an average particle diameter of 24.8 nm were obtained. Then, the prepared SAPO-11 was used in the oxidative desulfurization process. The oxidative desulfurization was studied using several factors affecting desulfurization efficiency, such as time (40, 60, 80, 100, and 120) min, amount of MO/SAPO-11 (0.3, 0.4, 0.5, 0.6, and 0.7) g/100 ml of simulated oil (100 ppm of dibenzothiophene), the amount of hydrogen peroxide (4ml) oxidizer/100 ml of simulated oil, and the temperature ranges from (40, 50, 60, 70, and 80 °C). The results showed that an increase in MO/SAPO-11 led to an increase in desulfurization. The best removal percentage for sulfur content was 92.79%, obtained at 70 °C and 0.6 g of MO/SAPO-11 containing 7.5% CNT, and the removal was 82.34% at 0% CNT and the same other conditions. While the equilibrium was achieved after 100 min. The results revealed that Freundlich’s model described the adsorption of sulfur compounds better than Langmuir’s, where the R2 of the Freundlich model was 0.9979 and the R2 of the Langmuir model was 0.9554.